The Effect of Using Letter Card Media On The Language Ability (Literacy) Of Children Aged 4-5 Years At RA Tsamaniatun Hasanah Medan-Binjai KM.13.5 In Academic Year 2021/2022 - Untari, Ladipa; Ladipa Untari (MultiTech Publisher, 2023)
The research aims to explain the significant influence of letter card media on the language (literacy) abilities of children aged 4-5 years at RA Tsamaniatun Hasanah for the 2021/2022 academic year. The research design uses one group pretest-posttest from the pre-experimental design. The population in this study were all class A children aged 4-5 years at RA Tsamaniaun Hasanah with a total of 15 children. The results of the research showed a total score (pre-test) of 65 and a total score (post-test) of 159. A comparison between the scores (pre-test) and the scores (post-test) of the experimental group was then analyzed and the result was W count = 0, W table = 25 with comparison conditions if W count 0 < 25 W table then Ho is rejected and Ha is accepted. Thus, the letter card media influences language skills (literacy) in class A RA TSAMANIATUN HASANAH Sei Semayang Village.